2020
DOI: 10.1111/apha.13444
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant sinus node firing during β‐adrenergic stimulation leads to cardiac arrhythmias in diabetic mice

Abstract: Aim: Cardiovascular complications, including cardiac arrhythmias, result in high morbidity and mortality in patients with type-2 diabetes mellitus (T2DM). Clinical and experimental data suggest electrophysiological impairment of the natural pacemaker of the diabetic heart. The present study examined sinoatrial node (SAN) arrhythmias in a mouse model of T2DM and physiologically probed their underlying cause. Methods: Electrocardiograms were obtained from conscious diabetic db/db and lean control db/+ mice. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…At present, the most objective, sensitive and reliable method to diagnose DNP is NET. NET electrophysiological examination is the gold standard for diagnosis, but the operation is complicated and costly (15)(16)(17)(18)(19), and if it is used as a routine examination item, patient compliance is poor. The screen efficiency of MNSI for DPN is better than that of the TCSS and the MNSI has the same diagnostic consistency with NET.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most objective, sensitive and reliable method to diagnose DNP is NET. NET electrophysiological examination is the gold standard for diagnosis, but the operation is complicated and costly (15)(16)(17)(18)(19), and if it is used as a routine examination item, patient compliance is poor. The screen efficiency of MNSI for DPN is better than that of the TCSS and the MNSI has the same diagnostic consistency with NET.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Lepr db/db or eNOS −/− alone do not replicate the optical action potential and arrhythmia phenotypes we observed in 2KO mice (combined Lepr db/db eNOS −/− ). Previous studies have shown that Lepr db/db mice exhibit slow conduction 61 , but evidence for spontaneous calcium release is conflicting 62 , 63 . Similarly, eNOS deficiency has been associated with fibrosis 64 , which may explain conduction slowing that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…These and similar digits were seen before, but were forced to trust and believe that they might have place in nature and science. How it is logical that the RR interval in ECG is apart at 106 versus 113 ms (Lubberding et al, 2020), but the PR and QRS are identical at respective 33 ± 1 and 11 ± 0.2 ms at the same time and conditions for two different groups, control − db/+ and diabetic − db/db mice in table 1? Are these digits, 216 ± 44 versus 260 ± 39% really not apart and statistically insignificant for db/+ versus db/db mice and carbachol effects on RR?…”
Section: Neither Ca2+ Clock Nor Hcn Is a Dominant Pacemakermentioning
confidence: 99%